Advancing proton FLASH radiation therapy: innovations, techniques, and clinical potentials - Ma, Yangguang; Zhang, Tengda; Selvaraj, Balaji; Shen, Jiajian; Wei, Shouyi; Cheng, Chingyun; Gao, Hao; Poulsen, Per Rugaard; Li, Heng; Diffenderfer, Eric; Schuemann, Jan; Lin, Liyong; et al. (International journal of radiation oncology, biology, physics, 2025)
Proton FLASH radiation therapy (RT) is an emerging technique that offers highly conformal doses similar to conventional intensity modulated proton therapy but with the added potential benefit of protecting organs at risk through the FLASH-sparing effect. This review examines recent advancements in proton FLASH-RT, including transmission beams (TB), single-energy Bragg peak, single-energy spread-out Bragg peak, hybrid FLASH, and multiple-energy spread-out Bragg peak. These proton FLASH technologies are discussed in detail, highlighting their advantages, limitations, and dosimetric comparisons with intensity modulated proton therapy and other FLASH techniques. Although TB achieves dose conformity through multifield optimization, it also has unnecessary exit doses. In contrast, single-energy Bragg peak and single-energy spread-out Bragg peak offer improved organ at risk protection and superior target conformity at the cost of using range compensators and/or ridge filters. Additionally, hybrid FLASH-RT combines TB and Bragg peak methods to target the tumor core and edges separately, whereas multiple-energy spread-out Bragg peak FLASH leverages ultra-fast energy switching. Despite these advancements, only nonconformal TB FLASH-RT has been applied clinically with single fields for palliative RT because of the complexity of other methods and uncertainties about the FLASH effect. This review summarizes the technical details of these FLASH-RT methods and discusses their utilization across various anatomical sites.
Online verfügbar: 11. Juni 2025, Artikelversion: 23. September 2025
Gesehen am 17.11.2025